The prevalence and impact of depression and anxiety in cardiac rehabilitation: A longitudinal cohort study. (March 2020) - Rao, A; Zecchin, R; Newton, PJ; Phillips, JL; DiGiacomo, M; Denniss, AR; Hickman, LD
Background: Co-morbid depression and anxiety symptoms are frequently under-recognised and under-treated in heart disease and this negatively impacts self-management. Aims: The purpose of this study was to determine the prevalence, correlates and predictors of depression and anxiety in cardiac rehabilitation programmes, the impact of cardiac rehabilitation on moderate depression, anxiety and stress symptoms, and the relationship between moderate depression, anxiety and stress symptoms and cardiac rehabilitation adherence. Methods: This was a retrospective cohort study of 5908 patients entering cardiac rehabilitation programmes from 2006–2017, across two Sydney metropolitan teaching hospitals. Variables included demographics, diagnoses, cardiovascular risk factors, medication use, participation rates, health status (Medical Outcomes Study Short Form-36) and psychological health (Depression Anxiety Stress Scales) subscale scores. Results: Moderate depression, anxiety or stress symptoms were prevalent in 18%, 28% and 13% of adults entering cardiac rehabilitation programmes, respectively. Adults with moderate depression (24% vs 13%), anxiety (32% vs 23%) or stress (18% vs 10%) symptoms were significantly less likely to adhere to cardiac rehabilitation compared with those with normal-mild symptoms ( p  < 0.001). Anxiety (odds ratio 4.395, 95% confidence interval 3.363–5.744, p  < 0.001) and stress (odds ratio 4.527, 95% confidence interval 3.315–6.181, p  < 0.001) were the strongest predictors of depression. Depression (odds ratio 3.167, 95% confidence interval 2.411–4.161) and stress (odds ratio 5.577, 95% confidence interval 4.006–7.765, p  < 0.001) increased the risk of anxiety on entry by more than three times, above socio-demographic factors, cardiovascular risk factors, diagnoses and quality of life. Conclusion: Monitoring depression and anxiety symptoms on entry and during cardiac rehabilitation can assist to improve adherence and may identify the need for additional psychological health support. Exploring the relevance and use of adjunct psychological support strategies within cardiac rehabilitation programmes is warranted.